New Evidence of the Purple‐Dye Industry at Tel Shiqmona, Israel. (21st February 2017) - Sukenik, N.; Iluz, D.; Amar, Z.; Varvak, A.; Bar, S.
Abstract : Pottery sherds stained with purple dye were found in the excavations at Tel Shiqmona, and were dated to the Iron Age II period. Analysis by HPLC‐DAD identified the dye as 'true purple', derived from the Hexaplex trunculus sea snail, which is associated with the purple‐dye industry that flourished in the coastal area at that time. This result is compatible with the classification of over 1000 Muricidae shells that were found in the excavation. Hexaplex trunculus constitutes 80% of this group, indicating that it was the most commonly used species in the dye production at Tel Shiqmona.